2017
DOI: 10.1051/matecconf/201712002013
|View full text |Cite
|
Sign up to set email alerts
|

A comparative life cycle assessment (LCA) of alternative material for Australian building construction

Abstract: Abstract. The use of wood is seen as a sustainable alternative to reduce environmental impacts in building and construction sector. The low quality hardwood logs from plantation thinning are enhanced by producing engineered wood such as laminated veneer lumber (LVL). Nevertheless, engineered wood requires the use of chemicals and energy that may reduce its environmental benefits. A life cycle assessment (LCA) was conducted to compare the environmental performance of LVL produced from forestry thinning and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…258 The results exhibit higher global warming potential (GWP) and embodied energy for LVL from mature logs than thinned logs. 258 Gonzaĺez-Garci ́a et al conducted a cradle-to-gate LCA for wood hardboard and identified that chemicals, electricity, and production of green chips have large contributions to environmental impacts. 259 Compared to the cradle-to-gate system boundary, the cradle-to-grave system boundary can be useful for understanding the impacts of use and end-of-life design, especially in the context of the circular economy.…”
Section: Basics Of Lca On Engineered Wood Productsmentioning
confidence: 94%
See 2 more Smart Citations
“…258 The results exhibit higher global warming potential (GWP) and embodied energy for LVL from mature logs than thinned logs. 258 Gonzaĺez-Garci ́a et al conducted a cradle-to-gate LCA for wood hardboard and identified that chemicals, electricity, and production of green chips have large contributions to environmental impacts. 259 Compared to the cradle-to-gate system boundary, the cradle-to-grave system boundary can be useful for understanding the impacts of use and end-of-life design, especially in the context of the circular economy.…”
Section: Basics Of Lca On Engineered Wood Productsmentioning
confidence: 94%
“…Lu et al chose the cradle-to-gate system boundary for a comparative LCA of laminated veneer lumber (LVL) made from thinned logs versus mature logs . The results exhibit higher global warming potential (GWP) and embodied energy for LVL from mature logs than thinned logs . González-García et al conducted a cradle-to-gate LCA for wood hardboard and identified that chemicals, electricity, and production of green chips have large contributions to environmental impacts .…”
Section: Lca Of Engineered Wood Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most important information tools for environmentally oriented product policy. The LCA can be defined as collecting and evaluating inputs, outputs and possible environmental impacts of the product system throughout the life cycle [29]. According to ISO 14040 and 14044, life cycle assessment is performed in four different phases.…”
Section: Introductionmentioning
confidence: 99%
“…LCA methodology found a broad application in decision supporting within the environmental sustainability context due to numerous initiatives launched at national and international levels (UNEP, SETAC, …) in order to facilitate and support its application (Bjørn et al, 2018). Nowadays LCA, covering wide range of domains (energy sector, building industry, agriculture, waste management and others), is widely used within the environmental studies (Góralczyk, 2003;Perminova et al, 2016;Tricase et al, 2017;Hossain et al, 2017;El Hanandeh et al, 2017;Dijkman et al, 2018).…”
Section: Life-cycle Assessment: a Short Literature Reviewmentioning
confidence: 99%